Who's in Charge Here? Direct and Indirect Accusations and Voter Punishment of Corruption. (June 2016) - Winters, Matthew S.; Weitz-Shapiro, Rebecca
There is a growing consensus that voters withdraw support from a politician when they receive clear information that the politician has engaged in corruption. But will voters punish an elected official for corrupt acts carried out under his or her watch even if the politician is not personally implicated in corruption? To answer this question, we present the results of an embedded experiment from a nationally representative survey in Brazil. Using vignettes that describe a hypothetical mayor, we find that citizens punish all mayors who are linked to corruption but that punishment is attenuated when members of the municipal administration, and not the mayor per se, are charged with corruption. The difference is particularly pronounced when corruption information comes from a credible source and among politically sophisticated respondents. Our findings highlight that both the nature of information and the characteristics of citizens who receive that information have implications for political accountability.